THE ROLE OF TRUST AND PERCEIVED RISK IN ELECTRONIC COMMERCE - NICULA DANA LAURA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2014)
Trust and risk are very important in consumers' electronic commerce purchasing decisions. How do trust and risk affect an Internet consumer's purchasing decision? To answer this question I’ve developed a theoretical framework describing the trust-based decision-making process a consumer uses when making a purchase from a given site. Consumer disposition to trust, reputation, privacy concerns, security concerns, the information quality of the Website, and the company's reputation, have strong effects on Internet consumers' trust in the Website.